Business Competitiveness Based on Community Preferences in an Indonesian Private University: A Case Study of Garut Regency, Indonesia - Wati Susilawati; Risma Muhamad Ramdani; Rofi Solihin; Agus Riyanto; Dũng Anh Tran (Australasian Accounting, Business and Finance Journal, 2024)
This research aims to investigate business competitiveness in Indonesian private universities. This qualitative research used literature review and survey as the data collection methods. Using purposive sampling technique, the research sample involved high school students and parents of students in Garut regency. Conjoint analysis method was applied with the assistance of SPSS software. The research findings indicate that the primary attribute considered in selecting private universities is accreditation. The findings affirm that the accreditation attribute holds significant influence in decision-making, outweighing other attributes such as facilities, tuition fees, promotions, and college location. Furthermore, the research results also indicate that parents of high school students share similar preferences with the high school students regarding the importance of accreditation attributes. These findings indicate the importance of enhancing academic quality and facilities in private universities, which directly impacts public perception and future prospects of their education and survivability.
Keywords: Preferences; Facilities; Costs; Accreditation; Location; Promotion